Transculturation and hybrid subjectivities in Robinson Crusoe’s rereading’s - Moraes, Carla Denize (2020)
This work aims to carry out an analysis about the postcolonial rereading’s of the classic Robinson Crusoe (1719), by Daniel Defoe. The works Friday; or, the Other Island (1967), Michel Tournier’s novel, and Crusoe (1988), a Caleb Deschanel’s movie, contain a critical reflection about transculturation and its effects in the transformation process of the colonial identities and they are going to be studied by means of interact comparative analysis, aiming to determine and expose the way art gives new means to the past under the light of contemporary opinion to promote possible changes of perspective about the subjects involved in the colonial process. To support our reflections about transculturation and hybridism we guide ourselves by the studies of Fernando Ortiz (1983) and Nestor García Canclini (2013), respectively. Understanding art as a reflection of its context of production, I believe it can either reproduce its historic time imaginary or subvert the reality to give it new meaning. This way, I am going to demonstrate that contemporary art, when transcontextualize the plot and the characters, questions and reflects about the hegemonic discourse contained in the eighteenth-century narrative and, thus, collaborate with the efforts to decolonization of minds.